Ð¡Ð¾Ñ…Ñ€Ð°Ð½Ð½Ð¾ÑÑ‚ÑŒ Ð¼ÐµÑ€Ð¸ÑÑ‚ÐµÐ¼ Ð²Ð¸Ð½Ð¾Ð³Ñ€Ð°Ð´Ð° Ð¸ ÐºÐ°Ñ€Ñ‚Ð¾Ñ„ÐµÐ»Ñ Ð¿Ñ€Ð¸ Ð¸ÑÐ¿Ð¾Ð»ÑŒÐ·Ð¾Ð²Ð°Ð½Ð¸Ð¸ Ñ€ÐµÐ¶Ð¸Ð¼Ð¾Ð² Ð±Ñ‹ÑÑ‚Ñ€Ð¾Ð³Ð¾ Ð·Ð°Ð¼Ð¾Ñ€Ð°Ð¶Ð¸Ð²Ð°Ð½Ð¸Ñ - Shevchenko, N. A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The effect of the rapid freezing method using PVS2 vitrifying solution on potato and grape meristems was under study. There were presented the results of meristem integrity to the 5th day of culturing after cryopreservation.